Management model of Belumbang Tourism Village: Stakeholder perspective - Darmawijaya, I Gede; Sunarsa, I Wayan; Sekarti, Ni Ketut; Darmaputra, Putu Gede Eka; Seniartha, I Wayan (Journal of Tourism, Culinary, and Entrepreneurship (JTCE), 2025)
Tourist villages in Bali require a management model that accommodates the interests of all parties to ensure resources are allocated toward the shared goals of economic, socio-cultural, and environmental sustainability. Weaknesses in existing management models and foundational values prompted this study, which aims to explain stakeholder perceptions of the current management model in Belumbang Tourist Village and analyze and propose a management model relevant to the needs of all stakeholders. This research employs a qualitative approach, using in-depth interviews with purposively selected participants until data saturation was achieved. The collected data were analyzed using Stakeholder Analysis and Interpretative Phenomenological Analysis (IPA). The results show that the eight identified key stakeholders primarily need a formal tourism village management body. This body should be professionally managed, guided by a value system that is reinforced by mutual agreements and collective adherence. Consequently, the proposed management model for Belumbang Tourist Village is one guided by customary village rules (perarem). These rules are founded upon a system of values built from the collective interests of all stakeholders. The model is designed to be implemented by a managing institution dedicated to achieving economic, socio-cultural, and environmental benefits and long-term sustainability. Therefore, it is recommended that the Belumbang Customary Village and the Administrative Village coordinate to evaluate the village's tourism performance and establish a professional management body. Further research is suggested to develop technical guidelines for the implementation of this management model.